Uji Efek Tabir Surya Ekstrak Etanol Biji Pinang (Areca catechu L.) Secara In-Vitro dengan Menggunakan Spektrofotometer UV-Vis - Khairuddin Khairuddin (Biocelebes, 2008)
The compound of sunscreen substance generally used is synthetic material. However, synthetic material sometimes has negative effect when it is mixed into blood current. To avoid negative effect traditional cure, such as Areca kernel can be used. A research has been done aiming to know the degree of effect value SPF sunscreen achieved from extract Areca kernel as sun protection factor for skin. The research done with extracting Areca kernel with reflux method in order to carry out component of chemical polyfenol as compound of sunscreen. Then, the extract is made soluted with concentration of 100 ppm, 200 ppm, and 300 ppm; then it’s 370 nm, following counting value SPF. The result of the research shows that all extract concentration of Areca kernel give value SPF, such as : that in the concentration of 100 ppm shows 2,19, concentration of 200 ppm shows 3,77, and concentration 300 ppm shows 5,63. Based on this research, it’s concluded that extract Areca kernel has sunscreen effect due to value SPF achieved fulfills in range sunscreen requirement, namely 2 to 60. Key words: Areca catecu, Sunscreen, Sun Protection Factor (SPF), Spektrofotometer UV-Vis